2013
DOI: 10.1177/1357633x13506513
|View full text |Cite
|
Sign up to set email alerts
|

Case study: the Interact home telehealth project

Abstract: Two home telehealth technologies (the Intel Health Guide and the Apple iPad) were trialled by four clinical services of the Hunter New England Local Health District. The iPad was selected by the Paediatric Palliative Care Service, the Stroke Service and the Brain Injury Rehabilitation Service. The Intel Health Guide was selected by the Cardiac Coaching Service. The telehealth devices were loaned to a total of 102 patients for different lengths of time, depending on clinical needs, but typically for about 3 mon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
48
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(48 citation statements)
references
References 0 publications
0
48
0
Order By: Relevance
“…Recent work [ 6 ] has also reported that participants connected via 4G mobile data services experience more audio and visual difficulties than participants on the NBN. Earlier work [ 7 ] reported similar problems with 3G connectivity in areas of poor signal strength. Since NBN rollout has been slow and patchy, current (and likely future) telehealth services will continue to rely on 3G/4G mobile services.…”
Section: Discussionmentioning
confidence: 65%
“…Recent work [ 6 ] has also reported that participants connected via 4G mobile data services experience more audio and visual difficulties than participants on the NBN. Earlier work [ 7 ] reported similar problems with 3G connectivity in areas of poor signal strength. Since NBN rollout has been slow and patchy, current (and likely future) telehealth services will continue to rely on 3G/4G mobile services.…”
Section: Discussionmentioning
confidence: 65%
“…In-depth interviews were conducted by the first author (J.W.) using an interview schedule [18,20] based on the research questions which allowed the interviewer to be prepared. However, there was participant freedom to express views with his/her own words and as a result the interview diverged from the interview guide and explored experiences of and feelings towards participant's experiences concerning access to use of an iPad [3].…”
Section: Data Generationmentioning
confidence: 99%
“…There are data to suggest these devices may be effective in improving: memory, an individual's sense of control, communication and overall independence [4,15,16]. There is very little evidence, if any, concerning the use of tablet technology use by stroke survivors [17,18].…”
Section: Introductionmentioning
confidence: 98%
“…Participants may have forgotten about the messaging system or found it too complex to use as multiple steps needed to be followed. Other tablet-based therapy studies with stroke patients have used teleconferences to stay in touch with patients [23,29], although this requires a high-quality internet connection that may not be available to all stroke survivors [20,23,29]. Other studies have opted to use face-to-face meetings [19] or group therapy sessions instead of relying on technology [17].…”
Section: Discussionmentioning
confidence: 99%
“…The ubiquity of smartphones, mobile application (apps), and mobile-tablet computers has brought along with it an interest in leveraging this technology for the purposes of providing stroke rehabilitation. There have been numerous studies focusing on mobile tablets as rehabilitation platforms for a variety of post-stroke deficits including communication [1422], cognition [16,23,24], fine-motor skills [2528]. Stroke survivors have typically expressed high satisfaction with tablet-based stroke therapies [14,15,18,20,24,25,2729] and have pointed to therapy independence [18,25,29] and the convenience of being able to engage in therapy at home [15,18] as specific positive aspects.…”
Section: Introductionmentioning
confidence: 99%